Effect Of Incorporation Of Either Neem Or Aloe Vera Powders On Tear Strength And Hardness Of Acrylic Soft Denture Liner Material (Mustansiria Dental Journal, 2022)
Aim of the study: The heat acrylic soft lining materials are far from ideal due to poor soften and weak tearing strengths. This cause some practical problems when testing the adherence of soft liners to denture bases. The study objective was to assess the effect of either Neem or Aloe Vera extracts on tear strength and hardness of heat acrylic soft denture lining material.Materials and methods: Sixty acrylic soft liner specimens were prepared and divided into two main groups (30 specimens for tear strength test, 30 specimens for hardness test). These main groups sub-divided into three groups, each one consist of 10 specimens, according to incorporated material. The hardness specimens were fabrication with dimensions of (30 mm diameter × 3 mm thickness). The tear strength specimens were fabricated according to ASTM specification D-624. The scanning electron microscope (SEM) was used to estimate the distribution of either Neem or Aloe Vera particles within the soft liner. Energy dispersive X-ray spectroscopy (EDS) was used to analysis the elements of studied materials. Tear strength specimens were measured by utilizing universal Instron machine. Hardness specimens were measured by utilizing Shore A durometer. Statically all data were analyzed by using SPSS software.Results: The outcomes showed non-significant differences (p>0.05) of all studied groups in tear strength and a highly significant (p